2016
DOI: 10.1007/s00359-016-1073-4
|View full text |Cite
|
Sign up to set email alerts
|

The final moments of landing in bumblebees, Bombus terrestris

Abstract: In comparison to other insects, like honeybees, bumblebees are very effective pollinators. Even though landing is a crucial part of pollination, little is known about how bumblebees orchestrate the final, critical moments of landing. Here, we use high-speed recordings to capture the fine details of the landing behaviour of free-flying bumblebees (Bombus terrestris), while landing on a flat platform with different orientations. We find that the bees have a fairly constant body and head orientation at the moment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
41
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 22 publications
6
41
0
Order By: Relevance
“…Our results confirm that bumblebees flying in still air follow a pattern of smooth deceleration consistent with that shown for honeybees [ Fig. 2; albeit on a somewhat different spatial scale (Baird et al, 2013), consistent with recent work in bumblebees (Reber et al, 2016)]. …”
Section: Effects Of Wind On Landing Speed and Body Orientationsupporting
confidence: 92%
“…Our results confirm that bumblebees flying in still air follow a pattern of smooth deceleration consistent with that shown for honeybees [ Fig. 2; albeit on a somewhat different spatial scale (Baird et al, 2013), consistent with recent work in bumblebees (Reber et al, 2016)]. …”
Section: Effects Of Wind On Landing Speed and Body Orientationsupporting
confidence: 92%
“…4C), increased rapidly with body size. Bumblebee workers have been found to approach artificial (Reber et al 2016) and natural flowers (Orth and Waddington 1997) from below, which would place the visual target dorsofrontally, a region where we also found that corneal IO angle decreases with eye size (Fig. 7A).…”
Section: Allometry Of B Terrestris Visual Fieldssupporting
confidence: 59%
“…2C) -in line with the analyses in Taylor et al (2016 & preprint). In B. terrestris this boundary is tilted around 10-18°further forward than the "long axis" of the head which has been used in behavioural studies to examine head position during flight and landing (Reber et al 2016). To our knowledge, there are no published data for the head pitch angle of bumblebees during free flight (i.e.…”
Section: Ocellar Fields Of Viewmentioning
confidence: 99%